Guidelines on The Development of The Guidelines of Further Study and Careers in Art Using Online Gamification - Ariyawatwong , Nahathai; Promphan, Intira (Silpa Bhirasri (Journal of fine arts), 2021)
Educational guidance for students who are interested in the arts, It is a factor that helps students to have better understanding about self awareness and the arts career. To illustrate, Appropriate age for receiving educational guidance is high school students because they must prepare for the university entrance exam. Therefore, the researcher wanted to find the guidelines of further study and careers in art for leaners who are interested in art to receive guidelines themself. By using online gamification to create continuity and interest in guidance. This research Aims to study and develop the guidelines of further study and careers in art using online gamification for high school students by using research methods to analyze the documents and related research. The results can be summarized at follow : 1. To study and analyze the art curricula of University in Thailand , Art careers and Career Qualifications. Art can be divided in to 3 branches: Fine Arts, Applied Arts and Art education 2. To design the structure of innovation by referring Frank Pasons' principles that is themselves, art careers analysis and decision to choose their career and plan their education by applying the elements of gamiification, there are 1. Goals 2. Rules 3. Feedback 4. Rewards, to stimulate students' interest in learning with a purpose to plan further education and suitable career in art for themselves.